Romanian Wormwood (Artemisia absinthium L.): Physicochemical and Nutraceutical Screening - Moacă, Elena-Alina; Pavel, Ioana Zinuca; Danciu, Corina; Crăiniceanu, Zorin; Minda, Daliana; Ardelean, Florina; Antal, Diana Simona; Ghiulai, Roxana; Cioca, Andreea; Derban, Mihnea; Simu, Sebastian; Chioibaş, Raul; et al. (Molecules (Basel, Switzerland), 2019)
Artemisia species are used worldwide for their antioxidant, antimicrobial and anti-inflammatory properties. This research was designed to investigate the phytochemical profile of two ethanolic extracts obtained from leaves and stems of A. absinthium L. as well as the biological potential (antioxidant activity, cytotoxic, anti-migratory and anti-inflammatory properties). Both plant materials showed quite similar thermogravimetric, FT-IR phenolic profile (high chlorogenic acid) with mild antioxidant capacity [ascorbic acid (0.02–0.1) > leaves (0.1–2.0) > stem (0.1–2.0)]. Alcoholic extracts from these plant materials showed a cytotoxic effect against A375 (melanoma) and MCF7 (breast adenocarcinoma) and affected less the non-malignant HaCaT cells (human keratinocytes) at 72 h post-stimulation and this same trend was observed in the anti-migratory (A375, MCF7 > HaCat) assay. Lastly, extracts ameliorated the pro-inflammatory effect of TPA (12-O-tetradecanoylphorbol-13-acetate) in mice ears, characterized by a diffuse neutrophil distribution with no exocytosis or micro-abscesses.